Acquisition and Evaluation of Rock Mass Geometric Data from Three-Dimensional Images for use in Geotechnical Analysis (2019)
In this paper, the application of a remote acquisition tool for sampling and measurement of discontinuities properties of rock masses, based on the interpretation of three-dimensional images, is evaluated. The applied method integrates a wide experimental plan in both, field and computer laboratory, to collect structural data such as orientation, persistence and spacing of discontinuities in a rock mass taken as a case study. Simultaneously, an intensive work of data collection in the field was carried out by conventional methodologies using compass and tape, for comparative purposes and statistical validation. The results allow to establish the advantages of using unconventional techniques, in terms of quality and quantity of information, as well as efficiency in terms of time spent for filed data collection. Through the semi-automatic analysis of three-dimensional images, geological mapping and objective characterization of discontinuities for geotechnical purposes were achieved, constituting a powerful tool with great potential for use in road and mining projects in Colombia.